2016
DOI: 10.1111/jsr.12411
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the improvement of insomnia on blood pressure in hypertensive patients

Abstract: Summary This study investigated the impact of the improvement of insomnia on the blood pressure levels of hypertensive patients. A total of 402 patients with a diagnosis of insomnia and hypertension were selected and randomly divided into two groups. The treatment group (202 cases) received standard anti‐hypertensive treatment with Estazolam, and the control group (200 cases) received standard anti‐hypertensive treatment with placebo. The sedentary diastolic and systolic blood pressures were measured before th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 38 publications
1
20
0
2
Order By: Relevance
“…Huang and associates demonstrated that a non‐benzodiazepine (zolpidem) significantly influenced the conversion of non‐dipping to dipping status when used for the management of insomnia . Li et al conducted a randomized, placebo‐controlled trial to evaluate the impact of estazolam on BP outcomes in patients with insomnia. Overall, 402 Chinese with insomnia and hypertension were randomly assigned to estazolam 1 mg/d (n = 202) and standard antihypertensive treatment or the later and placebo (n = 200).…”
Section: Studies On Insomnia Conducted Over the Last 2 Y Evaluating mentioning
confidence: 99%
See 1 more Smart Citation
“…Huang and associates demonstrated that a non‐benzodiazepine (zolpidem) significantly influenced the conversion of non‐dipping to dipping status when used for the management of insomnia . Li et al conducted a randomized, placebo‐controlled trial to evaluate the impact of estazolam on BP outcomes in patients with insomnia. Overall, 402 Chinese with insomnia and hypertension were randomly assigned to estazolam 1 mg/d (n = 202) and standard antihypertensive treatment or the later and placebo (n = 200).…”
Section: Studies On Insomnia Conducted Over the Last 2 Y Evaluating mentioning
confidence: 99%
“…18 Huang and associates demonstrated that a non-benzodiazepine (zolpidem) significantly influenced the conversion of non-dipping to dipping status when used for the management of insomnia. 19 Li et al 20 Of note, a post hoc analysis suggested that suvorexant resulted in a greater reduction in morning systolic ABPM compared with placebo among participants with baseline morning systolic ABPM > 150 mm Hg (P = 0.037). The most interesting finding of the study, however, may be the high prevalence of masked hypertension in this population (47% in both groups).…”
mentioning
confidence: 99%
“…Li et al . () report data from a study which compared standard antihypertensive treatment combined with a standard hypnotic in the United States (estazolam) with a control group who also received standard hypertensive treatment combined with placebo. This 4‐week treatment study showed that blood pressure decreased much more strongly in patients treated successfully with the hypnotic compared to the placebo condition.…”
Section: Insomnia: Self‐perception Spectral Analysis Hypertension mentioning
confidence: 99%
“…This allowed, as reported by the authors, more specific conclusions with respect to the influence of age and sex on the distribution of spectral power in insomniacs and good sleepers. Li et al (2017) report data from a study which compared standard antihypertensive treatment combined with a standard hypnotic in the United States (estazolam) with a control group who also received standard hypertensive treatment combined with placebo. This 4-week treatment study showed that blood pressure decreased much more strongly in patients ª 2017 European Sleep Research Society treated successfully with the hypnotic compared to the placebo condition.…”
Section: Insomnia: Sel F-per Ception Spectral Analysis Hyperten Siomentioning
confidence: 99%
“…This BP-lowering effect may have been caused by an improvement in sleep 4 or by reducing stress/anxiety and SNS arousal 5 . This approach should be tested in individuals with comorbid hypertension and insomnia.…”
mentioning
confidence: 99%